How Finance Penetrates its Other: A Cautionary Tale on the Financialization of a Dutch University. Issue 4 (26th March 2014) - Engelen, Ewald; Fernandez, Rodrigo; Hendrikse, Reijer
Abstract If any organization ought to be immune to the forces of financialization, it is a publicly funded university in corporatist Europe. Shielded from the intrusion by financial metrics, values and professionals through a strong historically rooted tradition of self‐management by powerful professional guilds, continental universities should largely have avoided the marketization and managerialization of Anglophone universities. Not so, this case study of a Dutch public university suggests. From 1995 onwards, a shift in real estate management—devolving responsibilities from the Dutch state to universities—served as a Trojan horse for financialization, triggering changes in organizational culture and a power shift from teaching and research professionals to accountants, real‐estate developers, financiers and their ilk. This case suggests that the power of finance is such that no societal domain is immune. The paper ends with a call for more non‐metropolitan case studies of financialization and argues that the only hope for salvation is a more self‐conscious defense of traditional academic values by the guardians of higher learning themselves.